The Effect of Work Discipline and Work Environment on Operational Performance through Work Motivation as a Mediating Variable in The Japanese Automotive Manufacturing Industry in Serang Regency - Eka Suprayogi; Ahmad Mukhlis; Udin Suadma (Sekolah Tinggi Ilmu Ekonomi Amkop Makassar, 2026)
Employees in manufacturing companies play an important role in maintaining operational performance and achieving production targets. However, low work discipline, inadequate work environments, and weak employee motivation may reduce company performance. This study aims to examine the effect of work discipline and work environment on operational performance, both directly and indirectly through work motivation as a mediating variable. This research employed a quantitative survey method. Data were collected from 88 employees working at Japanese automotive manufacturing companies located in the Modern Industrial Area of Cikande, Serang Regency, including PT Yasunaga Indonesia, PT Nippon Seiki Indonesia, and PT Mitsuba Indonesia, using questionnaires. The analysis was conducted using Partial Least Squares – Structural Equation Modeling (PLS-SEM) with SmartPLS 4 software. The results indicate that work discipline has a positive and significant effect on operational performance. Work discipline and work environment also have a positive and significant effect on work motivation. However, work environment does not have a significant effect on operational performance, and work motivation does not significantly influence operational performance. Furthermore, work motivation was not proven to mediate the relationship between work discipline and work environment on operational performance. The study concludes that strengthening work discipline remains the most important factor in improving operational performance, while motivation programs and work environment improvements should be continuously evaluated to create stronger impacts on employee productivity.